CHANGES IN THE LEVEL OF SEX HORMONES WITH AGING AND THEIR INFLUENCE ON THE VOICE - Petrovic Lazic, Mirjana; Ilic Savic, Ivana (HEALTH CARE, 2023)
The voice is considered an important secondary sexual trait that gives an independent seal to the character and personality of the individual. Disorders of the endocrine system in many cases affect the quality of the voice and can lead to numerous voice pathologies. The aim of this study is to review modern literature to provide an insight into contemporary research into the etiology, pathophysiology and symptomatology of changes in hormone levels associated with aging and their pattern-consequential relationship with voice quality, with special reference to the analysis of different types of mutations (mutatio precox and mutatio perversa), menstrual and climacteric dysphonia. The criteria for inclusion of works obtained from the search were: works published during the last 15 years, published in Serbian or English. Compared to the male voice, the female voice does not go through drastic changes during puberty. In males, the increased levels of testosterone and dihydrotestosterone during puberty are responsible for the enlargement of the laryngeal cartilage, which causes the basal tone to decrease by a third of an octave. If the child enters puberty prematurely, this hormone imbalance will lead to the appearance of voice pathology - mutation precox. Mutatio perversa occurs suddenly in females and is characterized by a deep male voice and other signs of virilization. The appearance of submucosal bleeding in the period before menstruation and the increased secretion of estrogen that leads to the appearance of edema will cause premenstrual dysphonia. Voice quality in this period is characterized by vocal fatigue, reduced voice range with loss of high tones, loss of vocal power and hoarseness of voice. Menopausal vocal syndrome is characterized by reduced flexibility and a reduced range of vibrational amplitude. It can be concluded that the vocal cords are a target organ, sensitive to fluctuations in the level of sex hormones due to the physiological aging process and the resulting endocrine disorders during life.